Using the Professional Judgment within the Financial Auditor's Profession - ADRIAN STEFAN-DUICU; VIORICA MIRELA STEFAN-DUICU (Global Economic Observer)
The audit mission comes to the aid of the big companies in solving the issues that occur in the financial statements. This paper aims to describe and synthesize the situations in which the auditor uses its professional judgment as a main instrument in the audit activity performed within a company. The professional judgment is a polyvalent concept that has implication on both the organizational level and the social, psychological, educational etc. The formation of such a judgment, even though it seems a flexible one, it needs accuracy and a perfect practice as a starting point.